PERUBAHAN MORFOLOGI BIBIT KARET (Hevea brassiliensis Muell. Arg.) TERHADAP INTERVAL PENYIRAMAN AIR PADA BERBAGAI MEDIA TANAM - Nurlaili, Nurlaili; Novriani, Novriani; Gribaldi, Gribaldi (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2017)
Seeds are healthy and fast according to the needs in the field is the composition of the media in the nursery and water availability. The composition of planting media soil, sand and organic matter. In addition to the growing medium, water also affects the growth of rubber plants. Treatment watering intervals, associated with the level of water availability. Plant growth improves with increasing amounts of water. In contrast, plant growth is hampered by lack of water is often associated with a reduction in the rate of photosynthesis. This study aims to determine the effect of watering intervals at different growing media on the growth of rubber seedlings. This study uses factorial completely randomized design, with five replications. -1 Factor is the growing media with a volume ratio (%), namely: M1 = Land (100%), M2 = Soil + sand (20% + 80%), M3 = Soil + sand + organic matter (10% + 80% + 10%), + M4 = Soil organic matter (20% + 80%). Factor-2 is an interval watering, namely: P1 = 4 days, P2 = 8 days, P3 = 12 days. Interval watering four days on the composition of soil organic matter 20% + 80% showed the highest yield at the variable plant height, number of leaf stems, root length, shoot dry weight, root dry weight and plant dry weight of rubber.